Potencial de utilização agrícola das águas salobras e residuárias da dessalinização por osmose reversa - Oliveira, André Moreira de (Universidade Federal Rural do Semi-Árido, 2011)
The brackish waters may represent a great potential in agricultural production profitable, depending on the adoption of proper cultural practices and the crop tolerance to salinity. Hydroponic systems can contribute to the production of vegetables when you use lower quality water, because the saturation state of the plants are subjected, enables increased tolerance of the same salinity. However, studies to be conducted in order to increase information about the use of brackish water in hydroponic systems, and also looking for information on levels of crop response to salinity are of fundamental importance to improve investment yields in hydroponics, especially in the Northeast Brazil. Given the lack of information for the crops of melons and tomatoes hydroponically, the objective was to investigate the potential use of brackish water and desalinator in such cultures. Two experiments were conducted with two melons and tomatoes in open hydroponic system in the greenhouse of the Universidade Federal Rural do Semi-arido (UFERSA) in Mossoró-RN. We evaluated the melon (Cucumis melo L.), cantaloupe, the AF 015, in terms of growth and production, the first experiment using saline waste with different levels of salinity throughout the cycle, and the second experiment the melon crop exposed to salt stress at different stages. The third and fourth experiments the culture was evaluated tomato (Lycopersicon esculentum L.), cherry, and tomato cultivar Fern Group Santa Cruz, Kada Gigante cultivar, respectively, using water desalinator in the nutrient solution in different dilutions, and latter at different stages of implementation. We used three different sources of water. The drinking water came from the public supply system that supplies the campus UFERSA. The brackish water was obtained from deep artesian well located in the Departmento de Ciências Ambientais of UFERSA. Already the desalination reject water was collected in the community Puxa Boi, located in Mossoró, RN. For the four experiments, we used a hydroponic system equipped with pots filled with coconut fiber, in which each vessel representing a separate plot. The application of brackish water and desalinator the nutrient solution of higher electrical conductivity, caused reductions in the growth and production of both the melon and tomato, but with no death of plants, showing the strength of the same water salinity this cropping system. It was also observed that at lower levels of salts, ie at higher dilutions with water supply, little or no significant difference was observed in the data collected. What can be considered as a viable alternative to the use of lower quality water when applied at dilutions of nutrient solution via hydroponic cultivation.
Potential agricultural use of wastewater and brackish water desalination by reverse osmosis
Keywords: Salinity; Osmotic adjustment; Hydroponics; Desalination reject; Salinidade; Ajuste osmótico; Hidroponia; Rejeito de dessalinização; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO